Ixodes chilensis Kohls, 1956 (Acari: Ixodida: Ixodidae) in Argentina - Cicuttin, Gabriel L.; Sebastian, Patrick; Lombardo, Maria Alejandra; Simone, Marcela; De Salvo, Maria Nazarena; Nava, Santiago (Elsevier, 2025)
The aim of this note is to report the first record of Ixodes chilensis Kohl, 1956 in Argentina. In June 2023, ticks were collected on bat belonging to the genus Histiotus from Dina Huapí, Rio Negro Province, Patagonian region, Argentina. Based on morphological characteristics and analysis of an obtained partial 16S rDNA gene sequence, these ticks (five nymphs) were determined as I. chilensis. This result represents the first record of this tick species outside Chile and expands the knowledge of its geographical distribution in the southern cone of South America.